2012
DOI: 10.1039/c2cc17027b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chirality induction to an achiral π-conjugated polymer by circularly polarized light

Abstract: A preferred-handed helical conformation was induced to poly(9.9-dioctylfluren-2,7-diyl) (PDOF) in a thin film form upon irradiation with single-handed circularly polarized light (CPL) where the induction was reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 31 publications
3
96
0
Order By: Relevance
“…Chemists have successfully realized the helical chirality switching by means of external stimuli, such as solvent, temperature, light irradiation, pH and so on. [21][22][23][24][25][26][27][28][29][30][31] In particular, intrinsic chirality exists in many organic solvents (e.g., limonene), and it tends to influence the solute conformation, then results in complete helical chirality inversion. Gin and Moore demonstrated that [This article is part of the Special Issue: Proceedings of 28th International Symposium on Molecular Chirality, Heidelberg 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Chemists have successfully realized the helical chirality switching by means of external stimuli, such as solvent, temperature, light irradiation, pH and so on. [21][22][23][24][25][26][27][28][29][30][31] In particular, intrinsic chirality exists in many organic solvents (e.g., limonene), and it tends to influence the solute conformation, then results in complete helical chirality inversion. Gin and Moore demonstrated that [This article is part of the Special Issue: Proceedings of 28th International Symposium on Molecular Chirality, Heidelberg 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Similar mechanisms have been proposed for photo-induced helixhelix transition of poly(BBPFA) and for CPL-assisted helix induction to a polyfluorene derivative. 25 It should be noted that the polymer behaved differently on irradiation in the absence of the scavenger under air, i.e., the sidechain alkyl group came off in the form of 2-methylbutanol (Fig. S4).…”
Section: Chart 1 Structure Of Poly(bmbpst)mentioning
confidence: 99%
“…Chirality induction for polyfluorene derivatives having no photochromic groups in thin film form upon irradiation of CPL was reported [19].…”
Section: Introductionmentioning
confidence: 99%